Mitochondrial DNA Analysis of Teeth for Identification of Natural Disaster Victims in Manila, Philippines - Victoria, Maria (Sriwijaya Journal of Forensic and Medicolegal, 2024)
Introduction: Natural disasters such as earthquakes, tsunamis and hurricanes often cause significant loss of life and damage to infrastructure. Identification of victims of natural disasters is an important aspect in the recovery process and forensic investigation. Mitochondrial DNA (mtDNA) has been proven to be an effective tool for individual identification due to its stable and maternally inherited nature. Teeth are an ideal source of DNA material for mtDNA analysis because they are durable against environmental degradation. This study aims to evaluate the effectiveness of mtDNA analysis of teeth for identifying victims of natural disasters in Manila, Philippines. Methods: Dental samples were collected from identified natural disaster victims and their family members. Mitochondrial DNA was extracted from teeth and analyzed using PCR and DNA sequencing techniques. The results of the mtDNA analysis were compared with mtDNA data obtained from family members to confirm the victim's identity. Results: Analysis of mtDNA on teeth succeeded in identifying all victims of natural disasters identified in this study. The mtDNA analysis results were consistent with mtDNA data obtained from family members, indicating the effectiveness of this method for individual identification. Conclusion: Analysis of mtDNA in teeth is a valuable tool for the identification of victims of natural disasters. This method can help in the recovery process and forensic investigations after natural disasters.